Faktor-Faktor Penyerapan Tenaga Kerja di Pulau Jawa - Silvia, Adelia; Susilowati, Dwi (Jurnal Ilmu Ekonomi JIE, 2023)
Problems that have not been resolved so far in Indonesia are related to employment. The increase in the number of job seekers is not proportional to the number of jobs available. This study aims to analyze factors related to employment in Java Island using three independent variables, namely gross regional domestic product, provincial minimum wage and human development index. This study uses combined data, namely time series data with a period of 10 years, namely 2011 to 2021 and cross section data with 6 provinces in Java Island. The method used is panel data regression. The results of the study show that regional gross domestic product, provincial minimum wage and human development index have a significant influence on employment in Java.   Indonesia masih menghadapi masalah penyerapan tenaga kerja. Jumlah pencari kerja yang meningkat tidak sebanding dengan jumlah pekerjaan yang tersedia. Produk domestik regional bruto, upah minimum provinsi, dan indeks pembangunan manusia adalah tiga variabel independen yang digunakan dalam penelitian ini. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara fakto-faktor penyerapan tenaga kerja di Pulau Jawa. Studi ini menggunakan data gabungan, yang mencakup data time series dari tahun 2011 hingga 2021, dan data cross-section dari enam provinsi Pulau Jawa. Indeks pembangunan manusia, upah minimum provinsi, dan produk domestik regional bruto memiliki pengaruh yang signifikan terhadap penyerapan tenaga kerja di Pulau Jawa.